THE EFFECT OF DISCOVERY LEARNING ASSISTED BY AUGMENTED REALITY ON FOURTH GRADE ELEMENTARY STUDENTS’ SCIENCE LEARNING OUTCOMES - Fharhah, Syilla Fhadlilla; Widiyono, Aan (STKIP Citra Bakti, 2026)
Prompted by the unsatisfactory academic performance of students regarding the abstract principles of force, this research aimed to evaluate the shifts in learning mastery following the integration of Augmented Reality-enhanced Discovery Learning. A quantitative methodology was adopted, utilizing a pre-experimental one-group pretest-posttest framework centered on 32 fourth-grade pupils. The primary data, derived from pre- and post-intervention evaluations, underwent rigorous analysis through a Paired Sample t-Test to determine the efficacy of the instructional tool. The results showed a significant difference between pretest and posttest scores with t(31) = -14.3, p < 0.001, as well as a Cohen’s d effect size of -2.53, indicating a large effect size. The students’ average scores increased from 63.7 to 87.0. These findings indicate an improvement in learning outcomes following the intervention. The implications of this study point to the need for further research using a design that includes a control group to strengthen the validity of the findings.